PENGARUH BEBERAPA JENIS ZPT DAN DURASI PERENDAMAN TERHADAP PERTUMBUHAN SETEK PUCUK TANAMAN JAMBLANG (Syzygium cumini (L.) Skeels) - Fanny Alya Shadika; Marai Rahmawati; Mardhiah Hayati (Jurnal Agrista, 2022)
Jambolan is a rare local fruit requiring an effective propagation technique to mantain its sustainability as vegetative propagation by cuttings. This study aims to determine the effect of plant growth regulator types and its soaking duration on jambolan cuttings growth. The study was conducted in Experimental Garden I and Plant Physiology Laboratory, Agriculture Faculty of Syiah Kuala University started from July to November 2021. The study used a 4 x 3 factorial completely randomized design. The factors studied were PGR types and soaking duration. The best jambolan cuttings growth caused by PGR was found in 40 gL-1 NAA treatment. The best jambolan cuttings growth caused by soaking duration was found in 10 hours soaking duration treatment. The best jambolan cuttings shoots growth was found in combination of 100% coconut water and 10 hours soaking duration treatment. The best jambolan roots growth was found in combination of 40 gL-1 and 8 hours soaking duration treatment. The Effect of Plant Growth Regulator Types and Soaking Duration on Jambolan (Syzygium cumini (L.) Skeels) Cutting Growth Jambolan is a rare local fruit requiring an effective propagation technique to mantain its sustainability as vegetative propagation by cuttings. This study aims to determine the effect of plant growth regulator types and its soaking duration on jambolan cuttings growth. The study was conducted in Experimental Garden I and Plant Physiology Laboratory, Agriculture Faculty of Syiah Kuala University started from July to November 2021. The study used a 4 x 3 factorial completely randomized design. The factors studied were PGR types and soaking duration. The best jambolan cuttings growth caused by PGR was found in 40 gL-1 NAA treatment. The best jambolan cuttings growth caused by soaking duration was found in 10 hours soaking duration treatment. The best jambolan cuttings shoots growth was found in combination of 100% coconut water and 10 hours soaking duration treatment. The best jambolan roots growth was found in combination of 40 gL-1 and 8 hours soaking duration treatment.